Integration of Psychology and Religion Toward The Suppression of Potential Crime - Muhammad Hasnan Nahar; Ihda Rufaida Nahar (Publication of the International Journal and Academic Research, 2024)
Religious psychology is a branch of psychology that examines the relationship between human behavior and the influence of the religious beliefs. The study focuses on aspects such as religious consciousness, religious experience, mental health, courage and faith to supernatural. By using a descriptive-qualitative method, this research explores the potential suppression of criminal acts influenced by the existence of jinayat laws in Islam. Punishment of whipping for adultery, hand-cutting for theft, death or crucifixion for robbery and qishaash for murder are exemplified the jinayat punishments.